Preliminary Study of Eels (Anguilla) in Sumbawa Island According to the Knowledge of Local Communities: Distributions, Pattern of Fishing, and Utilizations - Neri Kautsari; Husain Latuconsina; Ilham Zulfahmi (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research